Consumer Protection in Digital Transactions: Analysis of Potential Legal Voids - I Gusti Bagus Sakah Sumaragatha; Septira Putri Mulyana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Consumer protection is a crucial aspect of economic dynamics because it is related to guaranteeing the rights and interests of consumers as users of products and services. The goal is to ensure that consumers are not disadvantaged in transactions with businesses in the digital world. Consumer protection is not only a normative interest but also a strategic element in maintaining consumer trust in a rapidly evolving market. This is due to the continuous advancement of digital technology. The purpose of this study was to determine the existing regulations related to consumer protection and their practices in Indonesia in this digital technology era. Using normative research methods, this study can provide input to stakeholders regarding the revision of consumer protection laws. The study identified potential legal gaps in digital transactions, including attribution of responsibility, consumer data, standard clauses, and dispute resolution.